Fluid Consumption by Mexican Women during Pregnancy and First Semester of Lactation. (2nd February 2014) - Martinez, Homero
Abstract : The objective of this study was to describe daily fluid consumption in a sample of pregnant or lactating adult women. Women between 18 and 45 years of age, residents of Mexico City, stratified by socioeconomic status were asked to register their total fluid intake during 7 consecutive days. A total of 153 pregnant and 155 lactating women were recruited. On average, they drank 2.62 L/day and 2.75 L/day, respectively. Forty-one percent of pregnant women drank less than the recommended 2.3 L fluids/day, and 54% of women drank less than the recommended intake of 2.7 L/day during the first semester of lactation. Plain water contributed to 33% of total fluid intake, and sugar-sweetened beverages (SSB) contributed to 38% of total fluid intake. Up to 50% of pregnant and lactating women drank more than 1 L/day of SSB, which contributed to 632 kcal/day (27.5% of recommended dietary intake) and to 700 kcal/day (28% of recommended dietary intake), respectively. The high rates of overweight and obesity found in Mexican population, particularly among women, should alert us to the consumption of SSB during pregnancy and lactation, as excessive intake of these beverages may increase the risks of obesity, diabetes mellitus, and other chronic disorders.